Intravitreal Steroids for the Prevention of PVR After Surgery for Retinal Detachment - Gagliano, Caterina; D. Toro, Mario; Avitabile, Teresio; Stella, Santo; G. Uva, Maurizio (Current Pharmaceutical Design, 2015)
Proliferative vitreoretinopathy (PVR) can occur in eyes with rhegmatogenous retinal detachment (RRD) or after RRD surgery, and it is the most common cause of failure of this surgery, accounting for about 75% of all primary failures. Complex biological pathways induce PVR development, with growth factors and cytokines from the vitreous and from the serum (as a result of the breakdown of the blood-retinal barrier) stimulating RPE and Muller cells transformation and proliferation, and membrane formation and contraction. Identification of pre-operative risk factors, recognition of the early signs of PVR, use of adequate surgical techniques and of pharmacological therapy can reduce the PRV incidence. Steroids can influence the inflammatory and proliferative components of PVR, by reducing the breakdown of the blood-retinal barrier, and the proliferation of Müller cell and of RPE cells. Some new formulation of intravitreal steroids are promising tool for the prevention of the PVR formation in eyes treated by vitreoretinal surgery.
Keywords: retinal detachment